THE EFFORT TO INCREASE MATHEMATICS LEARNING ACTIVITY BY USING LEARNING COOPERATIVE MODEL OF NUMBERED HEAD TOGETHER (NHT) TYPE OF STUDENTS CLASS VIII - Ria Rahmatul Laili; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2018)
The students' lack of learning activity can be marked by lacking their enthusiasm, interaction, cooperation, and participation in the maths learning process. This research had the aim to increase the students learning activity using a cooperative learning model of NHT type. The research is a Classroom Action Research (CAR). The research subject is the VIII D of SMP Negeri 11 Yogyakarta on the even semester Academic Year 2016/2017. The object of the research is maths learning activity by using a cooperative learning model of NHT type. The technique used to collect the data is the observation method, interview method, test method, and triangulation. The research instruments were observation and interview papers. The research did twice cycles. The cycle was stopped after the indicator's result was reached out to> 60% or good criteria. The result of the research shown that maths learning by using a cooperative learning model of NHT type can increase the maths learning activity of the VIII D. Based on the result of the student's activity observation, where each learning process got an increasing percentage. The first achievement is 44.91 %. It means enough, and the other achievement became 67.83%. It means good. Based on the result of the interview, it is shown that there was a positive response to the students.